(untitled) (Acta Education, 2023)
Due to the cytotoxicity of carbon nanotubes (CNTs), there is an increasing need for functionalized CNTs (fCNTs) nowadays. Although a number of studies have been conducted to investigate the cytotoxic effects of fCNTs, their behavior in an aqueous medium has not been sufficiently studied. In this simulation-based research, the atomic level mechanisms of the interaction of pristine (non-functionalized) and fCNTs with water molecules were studied. The computational results showed that an increase in the number of functional groups in fCNT leads to an increase in its interaction energy with the water environment. This, in turn, results in a decrease in the cytotoxicity of fCNT. Overall, the results of the study contribute to the understanding at the molecular level of the transport and delivery of biological drugs using CNTs in the field of biomedicine.